Agro-economic potential of capsicum with drip irrigation and mulching (SAARC Journal of Agriculture, 2014)
A field experiment was conducted during 2006-07 and 2007-08 at Precision Farming Development Centre, Indira Gandhi Agricultural University, Raipur, Chhattisgarh, India, to evaluate the production, potential and economics of capsicum (Capsicum annum L.) as influenced by drip irrigation and mulches. Experiment was laid out in a split-plot design replicated thrice with irrigation levels 1.0 Epan (Pan evaporation) through drip, 0.8 Epan through drip, 0.6 Epan through drip and 1.0 Epan with flood irrigation (FI) in main plot and mulches (i.e. no mulch (Glyphosate @ 6.0 ml l-1 followed by 2 hand weedings), black polythene mulch (BPM: 40 ? thickness), transparent polythene mulch (TPM: 40 ? thickness), paddy straw mulch (PSM: 5 t ha-1) in sub plots. The growth parameters like plant height, number of primary and secondary branches, stem girth, leaf area, leaf area index, dry weight of leaf, stem, fruit and total dry weight were maximum with drip irrigation at 1.0 Epan followed by drip irrigation at 0.8 Epan. Among the mulches the maximum values of the growth parameters were noticed with black polythene mulch followed by paddy straw mulch. The yield attributes like fruit length, fruit volume, fruit girth, per cent fruit set, fruits/plant, green capsicum fruit weight and yields were higher with drip irrigation at 1.0 Epan followed by drip at 0.8 Epan. Among the mulches, all the yield attributes were found higher with black polythene mulch followed by paddy straw mulch; whereas least yield attributes were measured with no mulch. Marginal cost, marginal return, MR: MC, cost of cultivation, net returns and B: C were higher with drip irrigation at 1.0 Epan followed by drip irrigation at 0.8 Epan. Among different mulches all the economic parameters were higher with black polythene mulch followed by paddy straw mulch except MR: MC and B: C ratio. Capsicum with paddy straw mulch produced higher values of MR: MC and B: C ratios. DOI: http://dx.doi.org/10.3329/sja.v10i2.18323SAARC J. Agri., 10(2): 51-60 (2012)